The Levant, crossroads of late antiquity :history, religion and archaeology = Le Levant, carrefour de l'antiquite tardive : histoire, religion et archeologie - Aitken, Ellen Bradshaw, 1961-; Fossey, John M.; Kellaris, George.; Keiser, Jeffrey.; Bailey, Ryan.; Gauvin, Ginette. (McGill University Monographs in Classical Archaeology and History, 2014)
The Levant: Crossroads of Late Antiquity. History, Religion, and Archaeology / Le Levant: Carrefour de l'Antiquité tardive explores the monumental, religious, and social developments that took place in the Roman province of Syria during the Third through 6th centuries CE. Ellen Bradshaw Aitken and John M. Fossey bring together the work of twenty scholars of archaeology, art history, religious studies, and ancient history to examine this dynamic period of change in social, cultural, and religious life. Close attention to texts and material culture, including palaeo-Christian mosaics and churches, highlights the encounters of peoples and religions, as well as the rich exchange of ideas, practices, and traditions in the Levant. The essays bring fresh perspectives on "East" and "West" in antiquity and the diversity of ancient religious movements.